India and women's poetry of the 1830s: femininity and the picturesque in the poetry of Emma Roberts and Letitia Elizabeth Landon - ní Fhlathúin, Máire (Taylor & Francis, 2005)
This analysis of women’s writing on colonial India studies their work against the accounts of the picturesque and its function in colonial writing on India established by Sara Suleri and Nigel Leask. Roberts and Landon both work within this tradition, but ultimately find it inadequate to contain their explorations of domestic as well as colonial femininity. At this point, they supplement the poetic with other forms: prose versions, epigraphs or endnotes. These have the effect of drawing attention to and disrupting the ‘screen effect’ of the picturesque and explore those ‘more shattering aspects of [India’s] difference’ (Suleri), which it was normally the woman writer’s function to alleviate.